2021
DOI: 10.1111/hel.12865
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection and the progression of atherosclerosis: A systematic review and meta‑analysis

Abstract: Objective: In recent years, many studies have tried to prove whether Helicobacter pylori (H. pylori) can promote the progression of atherosclerosis (AS), but the reported results are conflicting. Carotid intima-media thickness (CIMT), flow-mediated dilation (FMD), or pulse wave velocity (PWV) are the most commonly used indicators to evaluate the progress of AS. So, we collected and evaluated these three indicators to provide evidence-based medicine for the clinic. Materials and methods:We included and evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…Infection with H.pylori is a major pathogenic factor for superficial gastritis, chronic atrophic gastritis, duodenal or gastric ulcers and gastric mucosa-associated lymphoid tissue lymphoma. 38 It has also been linked with several extra-digestive diseases such as atherosclerosis, 39 coronary heart disease, 40 iron deficiency anaemia, 41 idiopathic thrombocytopenic purpura, 42 vitamin B12 deficiency, 43 non-alcoholic fatty liver disease, 44 metabolic syndrome, 45 diabetes mellitus, 46 cerebrovascular disease, 47 Alzheimer’s disease, 48 Parkinson’s disease, 49 childhood asthma, 50 chronic obstructive pulmonary disease, 51 chronic urticaria, 52 rosacea 53 and osteoporosis. 54 H. pylori eradication is required for managing H. pylori -related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with H.pylori is a major pathogenic factor for superficial gastritis, chronic atrophic gastritis, duodenal or gastric ulcers and gastric mucosa-associated lymphoid tissue lymphoma. 38 It has also been linked with several extra-digestive diseases such as atherosclerosis, 39 coronary heart disease, 40 iron deficiency anaemia, 41 idiopathic thrombocytopenic purpura, 42 vitamin B12 deficiency, 43 non-alcoholic fatty liver disease, 44 metabolic syndrome, 45 diabetes mellitus, 46 cerebrovascular disease, 47 Alzheimer’s disease, 48 Parkinson’s disease, 49 childhood asthma, 50 chronic obstructive pulmonary disease, 51 chronic urticaria, 52 rosacea 53 and osteoporosis. 54 H. pylori eradication is required for managing H. pylori -related complications.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with angina pectoris have higher titers of anti-CagA antibodies compared to healthy controls [ 21 ]. Meta-analyses show an increased risk of atherosclerosis [ 26 ] as well as cardiovascular diseases, e.g., ischemic stroke and myocardial infarction, among H. pylori -positive subjects [ 20 , 27 ]. H. pylori -specific DNA has been detected in coronary atherosclerotic plaques [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…QHF consumption significantly increased the relative abundance of Bacteroides and Mucispirillum in mice feces, while it decreased the relative abundance of Escherichia-Shigella . Several studies have shown that microbiota with low Bacteroides abundance or high Helicobacter abundance can increase the risk of cardiovascular diseases [ 44 , 45 ]. In this study, QHF treatment significantly increased the relative abundances of Marvinbryantia and Phascolarctobacterium at the genus level.…”
Section: Discussionmentioning
confidence: 99%